Higher Education Internationalisation in Kazakhstan (2022-2023): Course Continuity or Change in the Focus? - A. M. Pogorelskaya; E. F. Troitskiy; V. S. Pakulin (Высшее образование в России)
The research aim is to evaluate the changes in Kazakhstan policy of higher education internationalisation due to the international relations transformation since February 2022. The research tasks are to identify the peculiarities of higher education internationalisation in Kazakhstan and to detect its main trends before and after 2022. Based on the definitions of higher education internationalisation formulated by J. Knight, P.G. Altbach et al., authors outline relatively successful attempts of Kazakhstan to follow world trends in higher education. However, research literature analysis suggests that there are still many problems in Kazakhstan higher education the Government is still unable to overcome due to the lack of resources.The authors confidently analyse the legal framework of higher education reform in Kazakhstan and decisively use event-analysis to identify the key characteristics of higher education internationalisation in Kazakhstan since its independence, during 1991-2023. The conclusion was that the country has been on a course of internationalisation since the 1990s, but that until 2010 it had been a point-by-point process. At the same time, a model of importing higher education services, mainly from Russia, was spontaneously formed. Since 2010, the second stage of internationalisation has begun, characterised by a large borrowing of Western models and practices, although the Western direction of interaction in higher education complemented, but did not replace, the Russian one. In 2022, Kazakhstan made an accelerated transition to the third stage of internationalisation of higher education, characterised by distancing itself from Russia, combining imports and ambitions to export higher education, and increasing competition with Russia for applicants.